Clinicopathological correlates of pyramidal signs in multiple system atrophy. Issue 7 (20th May 2022) - Lin, Chi‐Ying R.; Viswanathan, Anisha; Chen, Tiffany X.; Mitsumoto, Hiroshi; Vonsattel, Jean P.; Faust, Phyllis L.; Kuo, Sheng‐Han
Abstract: Objective: Pyramidal signs are common but often under‐recognized in multiple system atrophy (MSA). The clinicopathological correlates of pyramidal signs in MSA are not well characterized. The present study aims to understand the role of pyramidal signs in MSA. Methods: We examined 40 autopsy‐confirmed MSA cases in New York Brain Bank. The pyramidal signs were quantified by an established rating scale, summarized as the pyramidal score. We assessed whether pyramidal scores are associated with autonomic, parkinsonism, and cerebellar features and survival. We also examined whether the density of glial cytoplasmic inclusions (GCIs) in the motor cortex and its underlying white matter is associated with the pyramidal score. Results: MSA parkinsonian type cases have higher pyramidal scores compared to cerebellar type cases ( p  = 0.017). MSA cases with high pyramidal scores are more likely to have laryngeal stridor (OR = 4.89, p  = 0.022), but less likely to have orthostatic hypotension (OR = 0.11, p  = 0.006) and erectile dysfunction (OR = 0.05, p  = 0.018). MSA cases with high pyramidal scores do not differ from those with low pyramidal scores in terms of bowel dysfunction, dry eyes and mouth, and survival. Finally, MSA cases with more GCIs in the motor cortex have higher pyramidal scores compared to those with few GCIs ( p  = 0.017). Interpretation: Pyramidal signs in MSA are associated with the parkinsonian subtype, laryngeal stridor, and certain autonomic dysfunction.